Przemiany na rynku cebuli w latach 1995–2012 - Kraciński, Paweł (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2014)
The article presents changes on the onion market in the years 1995–2012. It shows production data which contain the level of harvest, yields, and sown area in the world and in Poland. The article analyses the main tendencies in international trade, taking into account the biggest exporters and importers and value and directions of onion foreign trade in Poland.